Compressive sampling methods for superresolution imaging - Fiddy, Michael A. (2013)
We investigate superresolution imaging using negative index metamaterials. Measurement of subwavelength scale features in the image domain is tedious and compressive sampling techniques are considered to alleviate this problem. A single detector (c.f. a single pixel camera geometry) is considered from which a high resolution image can be computed, which makes use of structured illumination for coding.